Leaf Spectral Reflectance Shows Thalassia testudinum Seedlings More Sensitive to Hypersalinity than Hyposalinity - Durako, Michael J.; Howarth, Jacqueline F. (Frontiers in Plant Science, 2017)
Thalassia testudinum (turtle grass) is the dominant and climax-successional seagrass species in the subtropical/tropical Atlantic and Caribbean region. Two die-offs of T. testudinum in Florida Bay, USA have raised concerns regarding the resilience of this species to environmental disturbances. Seedlings are important in recovery of T. testudinum, following disturbance events. Leaf spectral reflectance [R(λ)] was measured in T. testudinum seedlings exposed for two weeks to three salinities (20, 35, and 50) and two light levels (full sun and 50-70% light reduction) in experimental mesocosms. Multivariate analyses indicated that hypersalinity had a greater effect on spectral reflectance than hyposalinity or light reduction. There was an increase in variability and flattening of reflectance spectra at the highest salinity. All three salinity treatments had distinct reflectance spectra across green wavelengths (530 – 580 nm), with additional discrimination between 20 versus 50 and 35 versus 50 treatments across red wavelengths (630 – 690 nm). Red:Green reflectance ratios were highest and photochemical reflective index (PRI) values were lowest for the salinity 50 treatment, but were not significantly different between the salinity 20 and 35 treatments. The changes in the R(λ) spectra for the salinity 50 seedlings were consistent with previously observed reductions in leaf pigments and maximum photochemical efficiency of photosystem II. These observations indicate that leaf spectral reflectance is a sensitive indicator of plant stress in T. testudinum seedlings and that seedlings are more sensitive to short-term exposures to hypersalinity than hyposalinity.